2012
DOI: 10.1007/s11837-012-0250-3
|View full text |Cite
|
Sign up to set email alerts
|

A Materiomics Approach to Spider Silk: Protein Molecules to Webs

Abstract: The exceptional mechanical properties of hierarchical self-assembling silk biopolymers have been extensively studied experimentally and in computational investigations. A series of recent studies has been conducted to examine structure-function relationships across different length scales in silk, ranging from atomistic models of protein constituents to the spider web architecture. Silk is an exemplary natural material because its superior properties stem intrinsically from the synergistic cooperativity of hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 40 publications
1
69
0
1
Order By: Relevance
“…That being said, a molecular dynamics (MD) approach allows efficient manipulation of constitutive behaviour, such as elasticity and contact as well as interfacial failure and large deformation. As such, I use a coarse-grain mesoscopic 'bead-on-a-string' model as a platform to assess silk fibril behaviour, using general MD formulations [28,32]. Experimentally, it has been demonstrated that shearing of the silk protein solution can lead to a similar bead-on-a-string assembly at the nanometre scale [54,55].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…That being said, a molecular dynamics (MD) approach allows efficient manipulation of constitutive behaviour, such as elasticity and contact as well as interfacial failure and large deformation. As such, I use a coarse-grain mesoscopic 'bead-on-a-string' model as a platform to assess silk fibril behaviour, using general MD formulations [28,32]. Experimentally, it has been demonstrated that shearing of the silk protein solution can lead to a similar bead-on-a-string assembly at the nanometre scale [54,55].…”
Section: Methodsmentioning
confidence: 99%
“…'Could we be missing a critical structural feature, hidden in what we perceive as a structural flaw?' Undeniably, there is no single strategy allowing multi-scale stress transfer, and, like many biological materials [25][26][27], spider silk relies on a hierarchy of mechanisms to sustain strength and toughness across scales, from the nano-to macroscales [28]. In consideration of the fibril structure of silk, the question arises: can a little disorder-or structural heterogeneity-improve system performance?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Scheller et al, 2001 ) ‫دشٚسئ٥ٗ‬ ‫اص‬ ‫فبِ٣‬ ‫ٔذَ‬ ‫٤ه‬ ‫فٙىجٛر‬ ‫سبس‬ . ‫ف٥جش٢‬ ‫ٞب٢‬ ‫ص٤ؼش‬ ‫داسد‬ ‫ٔشاسج٣‬ ‫ػّؼّٝ‬ ‫ػبخشبس‬ ‫وٝ‬ ‫اػز‬ ٣ ‫د٥ٛ٘ذٞب٢‬ ‫ثب‬ ٚ ‫ضق٥ف‬ ‫ٔشوض‬ ‫دس‬ ‫ٞ٥ذسٚط٘٣‬ ‫عِٛ٣‬ ‫سغ٥٥شار‬ ‫ثٝ‬ ‫دبػخ‬ ‫دس‬ ‫سؿشٝ‬ ‫سفشبس‬ ‫سٙؾ٥ٓ‬ ‫دس‬ ‫داسد‬ ‫٘مؾ‬ ‫فٙىجٛر‬ ‫سبس‬ ( Tarakanova & Buehler, 2012 ) (Vollrath & Knight, 2001) . Motriuk-Smith et al, 2005;Rising et al, 2006 ) .…”
Section: ‫د٥ـشفز‬ ‫ٞب٢‬unclassified
“…Silk is biodegradable and, unlike synthetic high-performance fibers such as Kevlar, it is extremely lightweight. [10][11][12] The mechanical performance of spider silk is retained over a large temperature range (À66 to 100°C), exhibiting particularly interesting behavior at low temperatures. At the temperature of liquid nitrogen (À196°C), silk has been shown to increase its strength by 64% relative to its strength at room temperature.…”
Section: Properties Of Spider Silkmentioning
confidence: 99%